The Simile Style in Some Qur'anic Texts. A Rhetorical Study (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This research examines simile, considered among the miracle phenomena in the Glorious Qur'an. It is a kind of a figurative language and its role is comparing two unlike objects, but they subscribe something in common by using the words "like or as". It conveys an effective image, idea, situation, emotion and action to the listener in a creative and artistic way. It is used in everyday language and presents a colourful and an effective description. A simile is among the techniques used to express and convey the messages of the Holy Qur'an with the utmost clarity, beauty and impact. The Qur'anic similes come according to discourse requirements and speech purposes. This is the secret behind its semantic richness.The problem is embodied in finding simile expressions in the texts of Qur'an and revealing the extent at which they can convey the meaning for the listener with an effective and understandable way since it presents difficulties for non- specialists in studies of Arabic and Qur'an.The research aims at conveying and clarifying meanings as well as showing scientific facts in a way which enables the addressee to understand it. It also aims at sparking an important and enjoyable communication in readers or listeners mind.The study depends on just one hypothesis which is: a simile is a vital style of communication which increases eloquence and miracle of the speech. Texts of Qur'an contain different kinds of simile that cannot be realized easily.The chosen model for this research is Aj-Jundi. Within his book "Fin Al- Tashbih"(1952), he explains the rhetoric and a simile is one of the most important figures of rhetoric, i.e., stylistic ways for expressing the denoted meaning.The research includes seven divisions. An introduction is the first division. The concept of simile lies in the second one. The third division concentrates on the pillars of simile. The fourth examines the divisions of simile. The fifth one highlights the purposes. The sixth division deals with benefits of simile. The seventh one is a conclusion which contains findings this study has come up with.